The Influence of Materialism on Student's Lifestyle: A Case Study of a Rural-based University in Limpopo Province, South Africa - Mabina Karabo Suzan; Marubini Mukwevho (Noyam Journals, 2024)
Many students use their obsession with material possessions as a means of expressing their confidence and sense of self-worth. Therefore, the study looked at how materialism affected students' lives and academic achievement at a rural South African university in the province of Limpopo. To explore materialism's effects on students' lifestyles and academic performance a qualitative approach was adopted. The impact of materialism on students' lives and education was examined using an exploratory research design. The fourth-year male and female students were selected using a non-probability purposive sampling technique. Semi-structured in-person interviews were conducted to gather comprehensive data on the educational and lifestyle background of the students. The thematic analysis method was employed in the study to identify trends, and their lifestyles influencing the acquisition of numerous material possessions, leading to severe psychological and financial problems attributed to strained interpersonal relationships, low self-esteem, financial debt, and poor academic performance. Students are largely influenced by peer pressure, parental lifestyle, personality, culture, poverty and social media to spend a lot of money frivolously. Preoccupation with acquiring material goods leaves a trail of unpayable debts, mental illness and strained relationships. The study serves as an awareness creation campaign for various stakeholders such as tertiary institutions, parents, guardians, scholarships and bursary funders to intervene regarding materialistic attitudes.